Effect of micron (micronutrients) fertilizer on the growth and yield of Wheat variety Sarsabz - Hisbani, Wajid Ali; Solangi, Abdul Malik; Laghari, Mashooq Ali; Channa, Ghulam Murtaza (Journal of Scientific Agriculture, 2023)
The Department of Chemistry Soil Section Agriculture Research Institute, Tando Jam, conducted an examination in order to find out how micron (micronutrient) fertilizer affected the growth and yield of the wheat variety Sarsabz. Three replicates of a Randomized Complete Block Design were used to investigate the effects of micron (micronutrients) fertilizer utilized at rates of 0, 50, 100, and 150 kg ha-1 having a plot size of 46 m x 44 m. The results of the study revealed that applying micronutrient fertilizer to crops significantly altered the crop’s parameters. The application of Micron (micronutrients) fertilizer applied at a rate of 150 kg ha-1, with proposed N (168) and P (84) doses, resulting in the maximum wheat plant height (101.73), more tillers plant-1 (9.73), spike length (13.7), more grain spike-1 (51.66), heavier seeds (39.3), and higher grain yield (3453.3 kg ha-1). Therefore the micro nutrient is essential for achieving maximum yield production and should be applied with recommended doses on the wheat crop, performed better results in soil conditions of Tando Jam.